PERANAN MOTIVASIINTRINSIK DAN EKSTRINSIK DALAM MENINGKATKANINDEKS PRESTASIMAHASISWA FAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA - Dhamayantie, Endang (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2011)
Learning achievements attained an individual is the result of interaction between various factors that influence both from within (intrinsic motivation) or from outside (extrinsic motivation) individuals. This study aims to determine the effect of student motivation to learn which consists of intrinsic motivation (achievement, recognition of learning outcomes, responsibility, self-development) and extrinsic motivation (lecturer teaching methods, interaction with others, the condition of the college) on student achievement that is based on Grade Point Average (GPA). The research was conducted on students regular classes A and B of Faculty of Economics Department of Management, University of Tanjungpura. Samples were taken using a purposive sampling technique with criteria semester V upwards and is still actively attending. The number of samples was 98 students consisting of 49 regular A class and 49 regular B class. Data collection used questionnaires and data analysis techniques using multiple linear regression and independent sample t-test. The results showed that 1) intrinsic motivation of learning achievement (XI), recognition of learning outcomes (X2), responsibility (X3), self-development (X4) and extrinsic motivation of lecturers teaching methods (X5), interaction with others (X6) and the condition of the college (X7) simultaneously affect student achievement, 2) learning achievement (XI), recognition of learning outcomes (X2), lecturers teaching methods (X5) and the condition of the college (X7) partially affected on student achievement, 3) there was no difference in student achievement regular classes A and B. Keywords: Learning Motivation, Intrinsic Motivation, Extrinsic Motivation and Student Achievement.